Plays by Urals Young Playwrights: Everyday Life Description and Signs of Linguistic Naturalism - P. Jia (Научный диалог, 2018)
The aim of the research conducted on the texts of plays by young playwrights of the Urals is the identification of everyday life remarks as well as the ways of naturalistic description of the speech life of the city suburbs by the authors. It is noted that under the leadership of the playwright, director, actor Nikolay Kolyada, an aesthetic convention was developed, which is reflected in the analyzed works. The analysis of remarks allowed to systematize the speech means serving for the reliable description of life of the citizens included in the current time. Stylistic and linguoaxiological characteristic of dialogic interaction of the characters found ways and techniques of verbal portraiture, which is based on the method of linguistic naturalism. Particular attention is paid to the reproduction of the Ural urban vernacular, as well as jargonized vernacular. Replicas and dua-replicas containing crude expressives are distinguished. The functional analysis is made of the included in the structure of replicas rough and abusive vocabulary, contributing not only to the verbalization of negative emotions, but also to the rejection of typical Russian speech communication attitudes to cooperation, co-thinking, empathy. It is established that the activity of the units, remote from the literary center, indicates that young playwrights, processing life and language material, diagnose the crisis of modern speech communication.